Neighborhood Sustainability Assessment Tools: A Conceptual Framework For Their Use In Building Adaptive Capacity To Climate Change - Naji, Sally; Gwilliam, Julie (Zenodo, 2016)
Climate change remains a challenging matter for the human and the built environment in the 21st century, where the need to consider adaptation to climate change in the development process is paramount. However, there remains a lack of information regarding how we should prepare responses to this issue, such as through developing organized and sophisticated tools enabling the adaptation process. This study aims to build a systematic framework approach to investigate the potentials that Neighborhood Sustainability Assessment tools (NSA) might offer in enabling both the analysis of the emerging adaptive capacity to climate change. The analysis of the framework presented in this paper aims to discuss this issue in three main phases. The first part attempts to link sustainability and climate change, in the context of adaptive capacity. It is argued that in deciding to promote sustainability in the context of climate change, both the resilience and vulnerability processes become central. However, there is still a gap in the current literature regarding how the sustainable development process can respond to climate change. As well as how the resilience of practical strategies might be evaluated. It is suggested that the integration of the sustainability assessment processes with both the resilience thinking process, and vulnerability might provide important components for addressing the adaptive capacity to climate change. A critical review of existing literature is presented illustrating the current lack of work in this field, integrating these three concepts in the context of addressing the adaptive capacity to climate change. The second part aims to identify the most appropriate scale at which to address the built environment for the climate change adaptation. It is suggested that the neighborhood scale can be considered as more suitable than either the building or urban scales. It then presents the example of NSAs, and discusses the need to explore their potential role in promoting the adaptive capacity to climate change. The third part of the framework presents a comparison among three example NSAs, BREEAM Communities, LEED-ND, and CASBEE-UD. These three tools have been selected as the most developed and comprehensive assessment tools that are currently available for the neighborhood scale. This study concludes that NSAs are likely to present the basis for an organized framework to address the practical process for analyzing and yet promoting Adaptive Capacity to Climate Change. It is further argued that vulnerability (exposure & sensitivity) and resilience (Interdependence & Recovery) form essential aspects to be addressed in the future assessment of NSA's capability to adapt to both short and long term climate change impacts. Finally, it is acknowledged that further work is now required to understand impact assessment in terms of the range of physical sectors (Water, Energy, Transportation, Building, Land Use and Ecosystems), Actor and stakeholder engagement as well as a detailed evaluation of the NSA indicators, together with a barriers diagnosis process. : {"references": ["S. Eriksen, P. Aldunce, C. S. Bahinipati, R. D. Martins, J. I. Molefe, C. Nhemachena, K. O'Brien, F. Olorunfemi, J. Park, L. Sygna, and K. Ulsrud, \"When not every response to climate change is a good one: Identifying principles for sustainable adaptation,\" Climate. Dev., vol. 3, no. 1, pp. 7\u201320, 2011.", "N. L. Engle, \"Adaptive capacity and its assessment,\" Glob. Environ. Change. vol. 21, no. 2, pp. 647\u2013656, 2011.", "A. R. Edwards, \"Thriving Beyond Sustainability: Pathways to a Resilient Society,\" New Society Publishers, p. 38, 2010.", "N. L. Engle, \"The role of drought preparedness in building and mobilizing adaptive capacity in states and their community water systems,\" Climatic Change, vol. 118, no. 2. pp. 291\u2013306, 2013.", "H.-M. F\u00fcssel, \"Adaptation planning for climate change: concepts, assessment approaches, and key lessons,\" Sustain. Sci., vol. 2, no. 2, pp. 265\u2013275, 2007.", "G. C. Gallop\u00edn, \"Linkages between vulnerability, resilience, and adaptive capacity,\" Glob. Environ. Change. vol. 16, no. 3, pp. 293\u2013303, 2006.", "A. Bond, A. Morrison-Saunders, and J. Pope, \"Sustainability assessment: the state of the art,\" Impact Assess. Project. Appraisal, vol. 30, no. 1, pp. 53\u201362, 2012.", "M. Wilder, C. a. Scott, N. P. Pablos, R. G. Varady, G. M. Garfin, and J. McEvoy, \"Adapting Across Boundaries: Climate Change, Social Learning, and Resilience in the U.S.\u2013Mexico Border Region,\" Ann. Assoc. Am. Geogr., vol. 100, no. 4, pp. 917\u2013928, 2010.", "Y. Pan, R. a Birdsey, J. Fang, R. Houghton, P. E. Kauppi, W. a Kurz, O. L. Phillips, A. Shvidenko, S. L. Lewis, J. G. Canadell, P. Ciais, R. B. Jackson, S. W. Pacala, a D. McGuire, S. Piao, A. Rautiainen, S. Sitch, and D. Hayes, \"A large and persistent carbon sink in the world's forests.,\" Science, vol. 333, no. 6045, pp. 988\u2013993, 2011.\n[10]\tS. Hallegatte and J. Corfee-Morlot, \"Understanding climate change impacts, vulnerability and adaptation at city scale: An introduction,\" Climate. Change, vol. 104, no. 1, pp. 1\u201312, 2011.\n[11]\tE. L. Tompkins and W. N. Adger, \"Does Adaptive Management of Natural Resources Enhance Resilience to Climate Change?\" vol. 9, no. 2, 2004.\n[12]\tP. Van Der Linden, \"Climate Change 2007: Impacts, Adaptation and Vulnerability. Contribution of Working Group II to the Fourth Assessment Report of the Intergovernmental Panel on Climate Change,\" Intergov. Panel Climate. Change, vol. 4, p. 982, 2007.\n[13]\tR. Swart, \"Climate change and sustainable development: expanding the options,\" Climate. Policy, vol. 3, no. December 2014, pp. S19\u2013S40, 2003.\n[14]\tW. N. Adger, N. W. Arnell, and E. L. Tompkins, \"Successful adaptation to climate change across scales,\" Glob. Environ. Change, vol. 15, no. 2, pp. 77\u201386, 2005.\n[15]\tD. R. Godschalk, \"Urban Hazard Mitigation: Creating Resilient Cities,\" Nat. Hazards Rev., vol. 4, no. 3, pp. 136\u2013143, 2003.\n[16]\tJ. Blewitt, \"Community, Empowerment and Sustainable Development.\" 2008.\n[17]\tA. H. Abu Bakar and K. S. Cheen, \"A Framework for Assessing the Sustainable Urban Development,\" Procedia - Soc. Behav. Sci., vol. 85, pp. 484\u2013492, 2013.\n[18]\tB. L. Turner II, \"Vulnerability and resilience: Coalescing or paralleling approaches for sustainability science?\" Glob. Environ. Change, vol. 20, no. 4, pp. 570\u2013576, 2010.\n[19]\tD. Platts-fowler and D. Robinson, \"Neighborhood Resilience in Sheffield: Getting by in Hard Times,\" pp. 1\u201343, 2013.\n[20]\tE. Krasny and G.Tidball, \"Applying a Resilience Systems Framework to Urban Environmental Education, Environmental Education Research, \"Environmental education research,\"15.4: 465-482.2009.\".\n[21]\tA. Sharifi and Y. Yamagata, \"A conceptual framework for assessment of urban energy resilience - ResearchGate.pdf,\" Energy Procedia, no. November, pp. 1\u20137, 2015.5\n[22]\tB. Walker, S. Carpenter, J. Anderies, N. Abel, G. Cumming, M. Janssen, L. Lebel, J. Norberg, G. D. Peterson, and R. Pritchard, \"Resilience management in social-ecological systems: a working\\hypothesis for a participatory approach,\" Conservation. Ecol. [online], vol. 6, no. 1, p. 14, 2002.\n[23]\tT. Yigitcanlar and F. Dur, \"Developing a Sustainability Assessment Model: The Sustainable Infrastructure, Land-Use, Environment and Transport Model,\" Sustainability, vol. 2, no. 1, pp. 321\u2013340, 2010.\n[24]\tA. Sharifi and Y. Yamagata, \"Major Principles and Criteria for Development of an Urban Resilience Assessment Index,\" Int. Conf. Utility Exhibition. 2014, no. March, pp. 19\u201321, 2014.\n[25]\tM. Fleischhauer, \"The role of spatial planning in strengthening urban resilience,\" Resilience of Cities to Terrorist and other Threats: Proceedings of the NATO Advanced Research Workshop on Urban Structures Resilience under Multi-Hazard Threats: Lessons of 9/11 and Research Issues for Future Work. pp. 273\u2013298, 2008.\n[26]\tD. R. Nelson, W. N. Adger, and K. Brown, \"Adaptation to Environmental Change: Contributions of a Resilience Framework,\" Annual. Rev. Environ. Resources, vol. 32, no. 1, pp. 395\u2013419, 2007.\n[27]\tS. Tyler and M. Moench, \"A framework for urban climate resilience,\" Climate. Dev., vol. 4, no. May 2015, pp. 311\u2013326, 2012.\n[28]\tC. Folke, \"Resilience: The emergence of a perspective for social\u2013ecological systems analyses,\" Glob. Environ. Change, vol. 16, no. 3, pp. 253\u2013267, 2006.\n[29]\tI. M. C\u00f4t\u00e9 and E. S. Darling, \"Rethinking Ecosystem Resilience in the Face of Climate Change,\" PLoS Biol., vol. 8, no. 7, p. e1000438, 2010.\n[30]\tC. Folke, S. Carpenter, T. Elmqvist, L. Gunderson, C. S. Holling, and B. Walker, \"Resilience and sustainable development: building adaptive capacity in a world of transformations,\" Ambio, vol. 31, no. 5, pp. 437\u2013440, 2002.\n[31]\tR. Leichenko, \"Climate change and urban resilience,\" Current Opinion. Environ. Sustain, vol. 3, no. 3, pp. 164\u2013168, 2011.\n[32]\tF. S. Chapin, M. Hoel, S. R. Carpenter, J. Lubchenco, B. Walker, T. V Callaghan, C. Folke, S. a Levin, K.-G. M\u00e4ler, C. Nilsson, S. Barrett, F. Berkes, A.-S. Cr\u00e9pin, K. Danell, T. Rosswall, D. Starrett, A. Xepapadeas, and S. a Zimov, \"Building resilience and adaptation to manage Arctic change,\" Ambio, vol. 35, no. 4, pp. 198\u2013202, 2006.\n[33]\tW. N. Adger, \"Vulnerability,\" Glob. Environ. Change, vol. 16, no. 3, pp. 268\u2013281, 2006.\n[34]\tS. Cohen, J. Demeritt, J. Robinson, and D. Rothman, \"Climate change and sustainable development: towards dialogue,\" Global Environmental Change, vol. 8, no. 4. pp. 241\u2013371, 1998.\n[35]\tA. Kreimer, M. Arnold, and A. Carlin, Building Safer Cities Building Safer Cities\u202f: no. 3. 2003.\n[36]\tG. M. MacDonald, \"Water, climate change, and sustainability in the southwest,\" Proc. Natl. Acad. Sci., vol. 107, no. 50, pp. 21256\u201321262, 2010.\n[37]\tIpcc, Climate change and water: IPCC Technical Paper VI, vol. 403, no. 3. 2008.\n[38]\tE. Wall and B. Smit, \"Climate change adaptation in light of sustainable agriculture,\" J. Sustain. Agric., vol. 27, no. 1, pp. 113\u2013123, 2005.\n[39]\tM. Lockwood, \"The political sustainability of climate policy: The case of the UK Climate Change Act,\" Glob. Environ. Change, vol. 23, no. 5, pp. 1339\u20131348, 2013.\n[40]\tN. P. Melville, \"Information Systems Innovation for Environmental Sustainability,\" MIS Q., vol. 34, no. 1, pp. 1\u201321, 2010.\n[41]\tJ. Ikeme, \"Equity, environmental justice and sustainability: Incomplete approaches in climate change politics,\" Glob. Environ. Change, vol. 13, no. 3, pp. 195\u2013206, 2003.\n[42]\tA. Shaw, S. Burch, F. Kristensen, J. Robinson, and A. Dale, \"Accelerating the sustainability transition: Exploring synergies between adaptation and mitigation in British Columbian communities,\" Glob. Environ. Change, vol. 25, no. November 2015, pp. 41\u201351, 2014.\n[43]\tD. Scott, G. McBoyle, A. Minogue, and B. Mills, \"Climate Change and the Sustainability of Ski-based Tourism in Eastern North America: A Reassessment,\" J. Sustain. Tour, vol. 14, no. 4, pp. 376\u2013398, 2006.\n[44]\tE. Wall and B. Smit, \"Climate change adaptation in light of sustainable agriculture,\" J. Sustain. Agric., vol. 27, no. 1, pp. 113\u2013123, 2005.\n[45]\tJ. S. Damtoft, J. Lukasik, D. Herfort, D. Sorrentino, and E. M. Gartner, \"Sustainable development and climate change initiatives,\" Cement and concrete research., vol. 38, no. 2, pp. 115\u2013127, 2008.\n[46]\tP. Z. W., Kundzewicz, L. J., Mata, N. W., D\u00f6ll, and Shiklomanov, \"The implications of projected climate change for freshwater resources and their management The implications of projected climate change for freshwater resources and their management,\" Hydrology. Sci. J., vol. 53, pp. 37\u201341, 2008.\n[47]\tR. A. Matthew and A. Hammil, \"Sustainable Development and Climate Change,\" Int. Affordance., vol. 85, no. 6, pp. 1117\u20131128, 2009.\n[48]\tM. Pelling and D. Manuel-Navarrete, \"From resilience to transformation: The adaptive cycle in two Mexican urban centers,\" Ecol. Soc., vol. 16, no. 2, p. 11, 2011.\n[49]\tV. Bahadur, M. Ibrahim, and T. Tanner, \"The resilience renaissance? Unpacking of resilience for tackling climate change and disasters, SCR Discussion Paper 1,\" SCR Discuss. Paper, p. 45 pp., 2010.\n[50]\tT. P. Hughes, \"Climate Change, Human Impacts, and the Resilience of Coral Reefs,\" Science (80), vol. 301, no. 5635, pp. 929\u2013933, 2003.\n[51]\tS. Davoudi, K. Shaw, L. J. Haider, A. E. Quinlan, G. D. Peterson, C. Wilkinson, H. F\u00fcnfgeld, D. McEvoy, and L. Porter, \"Resilience: A Bridging Concept or a Dead End? 'Reframing' Resilience: Challenges for Planning Theory and Practice Interacting Traps: Resilience Assessment of a Pasture Management System in Northern Afghanistan Urban Resilience: What Does it Mean in Planning,\" Planning Theory & Practice, vol. 13, no. 2. pp. 299\u2013333, 2012.\n[52]\tJ. D. Graugaard, \"A tool for building community resilience? A case study of the Lewes Pound.,\" Local Environment, vol. 17, no. 2. pp. 243\u2013260, 2012.\n[53]\tM. E. Keim, \"Building Human Resilience,\" Am. J. Prev. Med., vol. 35, no. 5, pp. 508\u2013516, 2008.\n[54]\tM. R. Su, Z. F. Yang, B. Chen, and S. Ulgiati, \"Urban ecosystem health assessment based on energy and set pair analysis-A comparative study of typical Chinese cities,\" Ecological Modelling, vol. 220, no. 18. pp. 2341\u20132348, 2009.\n[55]\tN. L. Engle and M. C. Lemos, \"Unpacking governance: Building adaptive capacity to climate change of river basins in Brazil,\" Global Environmental Change, vol. 20, no. 1. pp. 4\u201313, 2010.\n[56]\tK. Vella, A. Dale, A. Cottrell, and M. Gooch, \"Assessing community resilience to climate change,\" 12th Int. Coral Reef Symposium, no. July, p. 5, 2012.\n[57]\tS. H. Eriksen and P. M. Kelly, \"Developing Credible Vulnerability Indicators for Climate Adaptation Policy Assessment,\" Mitigation. Adapt. Strategy. Glob. Change, vol. 12, no. 4, pp. 495\u2013524, 2007.\n[58]\tJ. Hinkel, \"'Indicators of vulnerability and adaptive capacity': Towards a clarification of the science-policy interface,\" Glob. Environ. Change, vol. 21, no. 1, pp. 198\u2013208, 2011.\n[59]\tC. Brown, Y. Giles, M. Laverty, and K. Li, \"Decision scaling: Linking bottom-up vulnerability analysis with climate projections in the water sector,\" Water Resources. Res., vol. 48, no. 9, pp. 1\u201312, 2012.\n[60]\tKelly, P. M., & Adger, W. N. (2000). Theory and Practice in Assessing Vulnerability To, 325\u2013352.\n[61]\tW. Adger, S. Huq, and K. Brown, \"Adaptation to climate change in the developing world,\" \u2026 Dev. Stud., vol. 3, pp. 179\u2013195, 2003.\n[62]\tW. N. Adger, N. Brooks, G. Bentham, M. Agnew, and S. Eriksen, \"New indicators of vulnerability and adaptive capacity,\" no. January, 2004.\n[63]\tN. Brooks, W. N. Adger, and P. M. Kelly, \"The determinants of vulnerability and adaptive capacity at the national level and the implications for adaptation,\" Glob. Environ. Change, vol. 15, no. 2, pp. 151\u2013163, 2005.\n[64]\tK. Vincent, \"Uncertainty in adaptive capacity and the importance of scale,\" Glob. Environ. Chang., vol. 17, no. 1, pp. 12\u201324, 2007\n[65]\tR. McLeman and B. Smit, \"Migration as an adaptation to climate change,\" Climate Change, vol. 76, no. 1\u20132, pp. 31\u201353, 2006.\n[66]\tH. M. F\u00fcssel and R. J. T. Klein, \"Climate change vulnerability assessments: An evolution of conceptual thinking,\" Climate Change, vol. 75, no. 3, pp. 301\u2013329, 2006.\n[67]\tC. Field, V. Barros, K. Mach, and M. Mastrandrea, \"Climate change 2014: impacts, adaptation, and vulnerability,\" \u2026 II Contrib. to IPCC \u2026, 2014.\n[68]\tF. Miller, H. Osbahr, E. Boyd, F. Thomalla, S. Bharwani, G. Zervogel, B. Walker, J. Birkmann, S. van der Leeuw, J. Rockstrom, J. Hinkel, T. Downing, C. Folke, and D. Nelson, \"Resilience and vulnerability: complimentary or conflicting concepts,\" Ecol. Soc., vol. 15, no. 3, p. 11, 2010.\n[69]\tA. L. Brenkert and E. L. Malone, \"Modeling Vulnerability and Resilience to Climate Change: A Case Study of India and Indian States,\" Climate Change, vol. 72, no. 1\u20132, pp. 57\u2013102, 2005.\n[70]\t C. Vogel, S. C. Moser, R. E. Kasperson, and G. D. Dabelko, \"Linking vulnerability, adaptation, and resilience science to practice: Pathways, players, and partnerships,\" Glob. Environ. Change, vol. 17, no. 3\u20134, pp. 349\u2013364, 2007.\n[71]\tK. O'Brien, S. Eriksen, A. Schjolden, and L. Nygaard, \"What's in a word? Conflicting interpretations of vulnerability in climate change research,\" Environ. Res., vol. 04, no. 2004:04, p. 16, 2004.\n[72]\tF. S. Chapin, G. Peterson, F. Berkes, T. V Callaghan, P. Angelstam, M. Apps, C. Beier, Y. Bergeron, a-S. Cr\u00e9pin, K. Danell, T. Elmqvist, C. Folke, B. Forbes, N. Fresco, G. Juday, J. Niemel\u00e4, a Shvidenko, and G. Whiteman, \"Resilience and vulnerability of northern regions to social and environmental change.,\" Ambio, vol. 33, no. 6, pp. 344\u2013349, 2004.\n[73]\tM. A. Janssen Michael L. Schoon, Weimao Ke etKaty Borner, \"Scholarly networks on resilience, vulnerability and adaptation within the human dimensions of global environmental change,\" Glob. Environ. Change, vol. 16, pp. 240\u2013252, 2006.\n[74]\tS. E. Williams, L. P. Shoo, J. L. Isaac, A. A. Hoffmann, and G. Langham, \"Towards an Integrated Framework for Assessing the Vulnerability of Species to Climate Change,\" PLoS Biology, vol. 6, no. 12, p. e325, 2008.\n[75]\tJ. Jordan, \"Rethinking community resilience to climate change: does a social capital lens help,\" Dev. Stud. Assoc. Conf., pp. 1\u201314, 2009.\n[76]\tT. Cannon and D. M\u00fcller-Mahn, \"Vulnerability, resilience and development discourses in context of climate change,\" Nat. Hazards, vol. 55, no. 3, pp. 621\u2013635, 2010.\n[77]\tJ. F. Johnstone, F. S. Chapin, T. N. Hollingsworth, M. C. Mack, V. Romanovsky, and M. Turetsky, \"Fire, climate change, and forest resilience in interior Alaska. This article is one of a selection of papers from The Dynamics of Change in Alaska's Boreal Forests: Resilience and Vulnerability in Response to Climate Warming.,\" Can. J. For. Res., vol. 40, no. 7, pp. 1302\u20131312, 2010.\n[78]\tE.D., Vugrin, D.E., Ehlen and R.C., Camphouse. \"A resilience assessment framework for infrastructure and economic systems_,\" Sustainable and Resilient Critical Infrastructure Systems, 77, 2011.\n[79]\tC. Perrings and D. I. Stern, \"Modelling loss of resilience in agroecosystems: Rangelands in Botswana,\" Environ. Resources. Econ., vol. 16, pp. 185\u2013210, 2000.\n[80]\tJ. Fiksel, \"SSPP: Sustainability and resilience: toward a systems approach,\" Sustain. Sci. Practice. Policy, vol. 2, no. 2, pp. 14\u201321, 2006.\n[81]\tJ. S. Mayunga, \"Understanding and Applying the Concept of Community Disaster Resilience\u202f: A capital-based approach,\" Landscape. Archit., no. July, pp. 22\u201328, 2007.\n[82]\tS. Derissen, M. F. Quaas, and S. Baumg\u00e4rtner, \"The relationship between resilience and sustainability of ecological-economic systems,\" Ecol. Econ., vol. 70, no. 6, pp. 1121\u20131128, 2011.\n[83]\tD. Childers, M. Cadenasso, J. Grove, V. Marshall, B. McGrath, and S. Pickett, \"An Ecology for Cities: A Transformational Nexus of Design and Ecology to Advance Climate Change Resilience and Urban Sustainability,\" Sustainability, vol. 7, no. 4, pp. 3774\u20133791, 2015.\n[84]\tC. J. Vorosmarty, \"Global Water Resources: Vulnerability from Climate Change and Population Growth,\" Science (80). vol. 289, no. 5477, pp. 284\u2013288, 2000.\n[85]\tB. L. Turner, R. E. Kasperson, P. A. Matson, J. J. McCarthy, R. W. Corell, L. Christensen, N. Eckley, J. X. Kasperson, A. Luers, M. L. Martello, C. Polsky, A. Pulsipher, and A. Schiller, \"A framework for vulnerability analysis in sustainability science.,\" Proc. Natl. Acad. Sci. U. S. A., vol. 100, no. 14, pp. 8074\u20138079, 2003.\n[86]\t T. Cannon, J. Twigg., & J. Rowell, \"Social Vulnerability, Sustainable Livelihoods and Disasters Report to DFID Conflict and Humanitarian Assistance Department,\" World, pp. 1\u201363, 2003.\n[87]\tJ. R. Lindsay, \"The determinants of disaster vulnerability: Achieving sustainable mitigation through population health,\" Natural Hazards, vol. 28. pp. 291\u2013304, 2003.\n[88]\tW. N. Adger, T. P. Hughes, C. Folke, S. R. Carpenter, and J. Rockstr\u00f6m, \"Social-ecological resilience to coastal disasters.\" Science, vol. 309, no. 5737, pp. 1036\u20131039, 2005.\n[89]\tJ. Hay and N. Mimura, \"Supporting climate change vulnerability and adaptation assessments in the Asia-Pacific region: an example of sustainability science,\" Sustain. Sci., vol. 1, no. 1, pp. 23\u201335, 2006.\n[90]\tI. M. Goklany, \"Integrated strategies to reduce vulnerability and advance adaptation, mitigation, and sustainable development,\" Mitigation. Adapt. Strategy. Glob. Change, vol. 12, no. 5, pp. 755\u2013786, 2007.\n[91]\tK. L. Larson, C. Polsky, and P. Gober, \"Vulnerability of Water Systems to the Effects of Climate Change and Urbanization: A Comparison of Phoenix, Arizona and Portland, Oregon (USA).\" pp. 179\u2013195, 2013.\n[92]\tB. L. Turner, R. E. Kasperson, P. A. Matson, J. J. McCarthy, R. W. Corell, L. Christensen, N. Eckley, J. X. Kasperson, A. Luers, M. L. Martello, C. Polsky, A. Pulsipher, and A. Schiller, \"A framework for vulnerability analysis in sustainability science.,\" Proc. Natl. Acad. Sci. U. S. A., vol. 100, no. 14, pp. 8074\u20138079, 2003.\n[93]\tA. Sharifi and A. Murayama, \"A critical review of seven selected neighborhood sustainability assessment tools,\" Environ. Impact Assess. Rev., vol. 38, pp. 73\u201387, 2013.\n[94]\tSaid, M. I. M., Zakaria, R., and Vikneswaran, M. (2009). The elements of sustainable urban neighborhood design. In Proceeding of the 7th Asia Pacific Structural Engineering and Construction Conference (pp. 4-6).\n[95]\tA. Sharifi and A. Murayama, \"Neighborhood sustainability assessment in action: Cross-evaluation of three assessment systems and their cases from the US, the UK, and Japan,\" Build. Environment, vol. 72, pp. 243\u2013258, 2014.\n[96]\tL. Sullivan, Y. Ridin, and C. Buchanan, \"Neighborhood Sustainability Frameworks - A Literature Review,\" no. May, p. 22, 2014. \n[97]\tA. Reith and M. Orova, \"Do green neighborhood ratings cover sustainability?\" Ecol. Indic., vol. 48, pp. 660\u2013672, 2015.\n[98]\tA. Garde, \"Sustainable by Design? Insights from U.S. LEED-ND Pilot Projects,\" J. Am. Plan. Assoc., vol. 75, no. 4, pp. 424\u2013440, 2009."]}